Analysis of training time optimization for self-driving car using alternate max pooling layers - Arefin, Kazi Ridwan; Huque, Md. Mashrukul; Tasin, Sheikh Sadaf; Khan, Ahmed Jawad; Abrar, Aareef (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.